STRATEGI CITY BRANDING KOTA SURABAYA SPARKLING SURABAYA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN - Arwanto, Caisar Pieter Vega; Nugraha, Bagus Setyawan; Widiyarta, Agus (PERSPEKTIF, 2020)
Research conducted by the author entitled "Surabaya City Branding Strategy" Surabaya Sparkling "In Increasing Tourist Visits". The purpose of this study is to find out how the Surabaya city branding strategy in increasing tourist visits. This is needed because the city of Surabaya has a lot of potential in the tourism sector such as parks in the city center, culinary tours, historic sites. The authors use Anholt's theory of general strategies in marketing or urban development and Kotler's hexagon city branding to find out how Surabaya's city branding strategy is in increasing tourist arrivals. The type of research used is the literature review where the research is in the library and study the literature which is the primary data source. The research approach uses descriptive qualitative analysis. The results of this study the Surabaya city government in increasing tourists, using the marketing strategy or promotion of city branding "Sparkling Surabaya" through the website, Instagram account, SSCT Bus, and holding events or activities one of them Car Free Day. This study concludes that the city branding strategy used is a marketing or promotion and event strategy, in increasing tourist visits.